Lived Experiences of Higher Education Instructors in Senior High School: Challenges and Impact on Professional Development - Creus, Mark Airon P.; Gatpandan, Mary Ann B.; Amboy, Janet Jay N.; Dulce, Gina B. (ASEAN Journal of Education, 2018)
School Year 2016-2017 ushered the beginning of the full implementation of Senior High School under K to 12 program of the Department of Education (DepEd). The said educational breakthrough and advancement has threatened the security of tenure of university teachers both from the public and private schools. DepEd opened the avenue for the displaced Higher Education Institution (HEI) college instructors by creating the demand for additional teaching personnel who will be deployed in the Senior High School. This study aims to have an in-depth understanding on different experiences of instructors from HEI teaching in senior high school, their challenges and impact on their professional development. The main sources of data were from the interviews and focus group discussion participated in by the teachers who came from both public and private higher education institutions. Thematic analysis was conducted to analyze and interpret the results of this study. Findings from the study showed themes based from the experiences of former college and university instructors who are currently teaching in senior high school. These are The Compass: Senior High School Teachers’ as Lifelong Learner, The Wind and the Waves: Teachers’ Challenges as a Lifelong Learner, and Ride the Waves: Opening Opportunities to Pioneer Senior High School Teachers. Teachers encountered different challenges like a shift in school culture, school climate and work habits. Support system from the school administrators and the entire government agency was perceived as having a great impact on the professional development of the teachers currently deployed in the senior high school.